2022
DOI: 10.1177/10760296221086283
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Platelets Activation Prior to Second Doses of Covid-19 Vaccine After Vaccine-Induced Immune Thrombotic Thrombocytopenia

Abstract: A recent letter to the editor published in the New England Journal of Medicine reports the safety of administration of a second dose of Covid-19 vaccine in patients with vaccine-induced immune thrombotic thrombocytopenia (VITT) following ChAdOx1 nCoV-19. None of the 40 cases who received a second dose has developed complication regardless of the vaccine received. 1 However, it is unclear if these patients were anticoagulated at that time or if platelet-activation assays remained positive prior to vaccination. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
2
0
0
Order By: Relevance
“…Clinically symptomatic thrombosis or increase in anti-PF4-heparin IgG ELISA did not occur in any patient (Figure 2). This is in keeping with other reported studies 6,7 including 40 patients, of which 26 had confirmed VITT and others had probable (2 patients) or possible (12 patients) VITT. 7 Cerebral venous sinus thrombosis is a relatively rare and unusual site of venous thromboembolism (VTE), with estimated incidence around 2.85-3.16 cases per 100,000 of hospitalized patients per year, which represents a distinct cause of stroke primarily affecting young adults.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Clinically symptomatic thrombosis or increase in anti-PF4-heparin IgG ELISA did not occur in any patient (Figure 2). This is in keeping with other reported studies 6,7 including 40 patients, of which 26 had confirmed VITT and others had probable (2 patients) or possible (12 patients) VITT. 7 Cerebral venous sinus thrombosis is a relatively rare and unusual site of venous thromboembolism (VTE), with estimated incidence around 2.85-3.16 cases per 100,000 of hospitalized patients per year, which represents a distinct cause of stroke primarily affecting young adults.…”
supporting
confidence: 92%
“…This is in keeping with other reported studies 6 , 7 including 40 patients, of which 26 had confirmed VITT and others had probable (2 patients) or possible (12 patients) VITT. 7 Of these 40 patients, the majority (33/40) received BNT162b2 (Pfizer–BioNTech) and the others ChAdOx1 nCoV‐19 (5/40) or mRNA‐1273 (Moderna) (2/40) as their second dose.…”
supporting
confidence: 92%